Dinâmica da infestação, abordagem semiológica e tratamento das infestações por Rhabditis spp. e Raillietia spp. em bovinos Gir, Minas Gerais, 2010 - Patricia Vieira Bossi Leite (2010)
The study took place in Teófilo Otoni municipality, MG, Brazil from august 2008 to august 2009. Experiment A evaluated dynamic of the parasitic infection caused by the nematode Rhabditis spp. and the mite Raillietia spp. It were used sixty four animals of a dairy herd, Gir breed, males and females, age ranging from 04 to 33 months. Every three months, material of the external auditory canal of all the animals was collected by flushing the right ear and at the same time the left ear was swabbed in order to observe the presence of parasites. The frequency of total positives for Rhabditis spp was 9.4 to 10.9% in the first three collections, increasing to 18.8 and 29.7% in the second and third collections respectively. The higher frequency found was 52.2% in the last sampling of the group 3. Results showed a positive correlation between frequency rate and age of the animals. Regarding the parasitic disease caused by Railiettia spp. It was observed that 42.2% of the animals were infested with parasitic intensity ranging from 1 to 13 mites per animal. In subsequent samplings, it was observed a decrease in the total of positive animals and parasite loads, suggesting interference of the sampling method on mite population. The study showed that the ear flushing was more efficient to detect infestations caused by both parasites, including sub-clinical cases. Statistical analysis showed a negative correlation between climatic factors, number of animals infected by the nematode and the severity of ear infections. Furthermore, it was observed a positive correlation between climatic factors and parasitic disease caused by mites. In Experiment B, it were studied twenty-six pregnant cows, age ranging from 3 to 14 years when fourteen (53.8%) were parasitized bilaterally by Rhabditis spp. The maximum intensity of clinical signs observed was grade 3, classified as moderate. Six cows with clinical signs of otitis were submitted to a intensive treatment protocol which consisted of multi washing of the external auditory canal with modified Dakin's solution (sodium hypochlorite 0.025%) and 1:1 solution of alcohol-ether, plus topical organophosphorus larvicide/repellent (Fenitrothion 6.8%). Animals were observed for 135 days with treatments, initially every 10 days, then every 15 days and one more last treatment interval period of 30 days. All the animals, positive and negative for parasites, treated or untreated, were kept together throughout all the experimental period.